Barriers to the Implementation of Renewable Energy Policies in Indonesia: A Case Study of Solar Energy in Improving Energy Security - Yusril Yudi Safaat; Palupi Lindiasari Samputra (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The transition to renewable energy has become an urgent necessity to address the climate crisis and strengthen national energy security. Solar energy, as the most abundant renewable energy source in Indonesia, possesses significant potential to support energy security and the clean energy mix. However, its utilization remains very limited compared to its overall potential. This study aims to identify the barriers to renewable energy policy implementation in Indonesia, with a particular focus on solar energy development as part of efforts to enhance national energy security. A systematic review was conducted on 25 scientific publications screened from the databases ScienceDirect, Scopus, and SpringerLink. The findings indicate that the barriers to solar energy development include unfavorable regulations for investors, lack of financial and non-financial institutional support, low energy literacy among end-users, and high upfront costs. Furthermore, the study reveals that these barriers are geographically uneven. In Java, the predominant challenges are related to regulatory and technical aspects, while in regions such as Kalimantan, Nusa Tenggara, and Papua, the dominant issues involve institutional coordination, limited technical services, and unequal access to information. These findings underscore that solar energy policies have not yet been designed or implemented in a manner responsive to local contexts, thereby constraining their potential contribution to strengthening national energy security.